Pendampingan Anak Korban Kekerasan dan Eksploitasi Seksual Melalui Trauma Healing dengan Media Teater di Kota Surakarta - Nining Sholikhah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Child is a person who is not yet 18 (eight) years old. Sexual violence is a crime of humanity. Violence and sexual exploitation of children must be stopped, because it is a crime against humanity and harms the dignity of children. Sexual violence against children in Indonesia has been classified as an extraordinary crime. The fact of the high sexual violence against children occurred in almost all of Indonesia and also occurred in the city of Surakarta. KAKAK Foundation carries out prevention and trauma healing (recovery) programs for child victims, as a form of contribution in creating the best life order for children. Through the Program, KAKAK Foundation conducted outreach and assistance to 152 victims of sexual exploitation of children in 1999-2004, 110 children, in 2005-2008, and 76 children in 2008-2011. The choice of children participation methods was very important in the prevention and trauma healing program (recovery) of children victims of sexual violence. For this reason, the program "Theater, As a Form of Child Participation in the Prevention and Trauma Healing of Children Victims of Violence and Sexual Exploitation" is carried out. Through theater children victims are actively involved (participative) in expressing their feelings and can voice children's aspirations to others.